A Training Program to Develop the Endurance Strength and Effect of the Enzyme Sgot and the Level of Some Performance Some of the Complex Skills in the Basketball for Youth - Hasan Saleh Mahdi Al-Okbi (Journal of Global Pharma Technology, 2016)
The objective of the research is to prepare a training program to develop the endurance of the strength, as well as to know the effect of this program on the enzyme SGOT and the level of performance of some skills in the basketball youth. The study sample consisted of (12) players, selected from the total community of (14) players, has been excluded (2) player for the purpose of conducting the exploratory experiment, and the experimental method was used to suit the nature of the research procedures. After the tests were carried out and the application of the training program was carried out the post-test to obtain the results through which the most important conclusions were reached. The researchers concluded that there was a significant effect of the training curriculum in the development of strength endurance of the muscles of the arms, increased rates of SGOT enzyme, and the emergence of a significant development in the level of performance of offensive youth composite basketball skills.Keywords: Endurance strength, Enzyme (SGOT), Complex offensive skills and basketball.